Kesaksian Perempuan dalam Tindak Pidana Pembunuhan: Studi Perbandingan Mazhab al-Syafi’i dan Mazhab Zahiri - Ramadani, Siti Makhfirah; Erlina, Erlina (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The main problem in this study is How Women's Testimony in the Case of the Crime of Murder (Comparative Study of the Syafi'i School and the Zahiri School)¸ which is formulated into several problem formulations as follows 1). What is the position of women in Islam, and 2). What are the views of the Shafi'i and Zahir schools regarding the testimony of women in the crime of murder. To answer the main problems above, a research is used in the form of Library Research, using sharia normative and conceptual research. The legal materials used are primary legal materials and secondary legal materials. In this thesis, data collection methods are used by means of identification, namely grouping data or searching for materials. The literature according to the title of the study, data reduction in this case selects and sorts data that is relevant to the discussion. The results of this study explain that the testimony of women in the crime of murder, namely the Syafi'I School believes that women should not be witnesses in the crime of murder. Meanwhile, the Zahiri School allows the testimony of women in the crime of murder. From the analysis of these two schools, I choose the opinion of the Zahiri School which allows women's testimony in cases of murder crimes because the law of carrying out testimony in Islam is fardu kifayah, including testimonies by women. the reality now is that the role of women is almost equal to the role of men, in almost all fields, because women also have almost the same access as men, where women are now public leaders, even presidents. By following the times, women should be equal with men before the law, including in their position as witnesses in all cases, both Muamalat, Munakahat, and Jinayat specifically in the field of Hudud and Qisas. With the provision of one male witness with two female witnesses who are just or four female witnesses who are just. Because the thing called jinayah must often happen around us, or we ourselves have experienced it, so that we can decide things according to what has been determined by Allah SWT.